1998
DOI: 10.1002/stab.199801870
|View full text |Cite
|
Sign up to set email alerts
|

Zur Berechnung von Verbundrahmen mit nachgiebigen Verbundknoten

Abstract: Anhand eines Beispieles wird die Berechnung eines unverschieblichen Verbundrahmens mit nachgiebigen Knoten im Bau‐ und Endzustand gezeigt. Dabei kann das nichtlineare Knotenverhalten mit Hilfe von entsprechenden Tabellenwerten für Steifigkeit und Tragfähigkeit dargestellt werden. Die Rahmenberechnung kann mit konventionellen EDV‐Programmen durchgeführt werden, wobei das Verhalten der Knoten durch entsprechende Ersatzstäbe simuliert wird. Die Deckungslinien für Riegel, Stützen und Knoten für verschiedene Lastsi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…However, due to the huge computational costs, the finite element method is not suitable for practical engineering design, especially when global frame analysis is required. The concept of the component-based method, in which a connection is divided into several components with known stiffnesses and strengths, was first proposed in 1980s [5], and then adopted in the design guidance [6]. Jaspart [7] summarized three principal steps of the componentbased method, which are (i) the identification of active components (such as endplate in bending, column web in compression, column flange in bending, bolts in tension); (ii) the characterisation of the active components, and (iii) the assembly of the active components into a connection model.…”
Section: Introductionmentioning
confidence: 99%
“…However, due to the huge computational costs, the finite element method is not suitable for practical engineering design, especially when global frame analysis is required. The concept of the component-based method, in which a connection is divided into several components with known stiffnesses and strengths, was first proposed in 1980s [5], and then adopted in the design guidance [6]. Jaspart [7] summarized three principal steps of the componentbased method, which are (i) the identification of active components (such as endplate in bending, column web in compression, column flange in bending, bolts in tension); (ii) the characterisation of the active components, and (iii) the assembly of the active components into a connection model.…”
Section: Introductionmentioning
confidence: 99%
“…An alternative simplified method that deals with the complexity of steel beam-to-column joints is the so-called component method (CM) coded in EC3-1-8 [3]. This method evolved from the work by Zoetemeijer [4] on bolted beam-to-column steel joints in the 1970s, which was subsequently extended by the Tschemmernegg's research group [5,6], Jaspart [7], Weynand et al [8] and several others -a thorough review of these developments may be found in Jaspart and Weynand [9].…”
Section: Introductionmentioning
confidence: 99%